2021
DOI: 10.3390/clinpract11020051
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of Multisystem Inflammatory Syndrome (MIS-C) in Children during the SARS-CoV-2 Pandemic in Latvia

Abstract: The total number of COVID-19 positive cases in Latvia has escalated rapidly since October 2020, peaking in late December 2020 and early January 2021. Children generally develop COVID-19 more mildly than adults; however, it can be complicated by multisystem inflammatory syndrome in children (MIS-C). This case study aims were to assess demographic characteristics and the underlying medical conditions, and clinical, investigative and treatment data among 13 MIS-C patients using electronic medical records. All 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Respiratory symptoms were rare, usually presenting with cough or dyspnea [8,9,42,43,46,47,49,51,54,57,60,62,69], or rhinorrhea [42]. Cardiac dysfunction [6, 29,43,71] was seen, with chest pain [9, 50] on presentation, myocarditis [8,43], and coronary artery dilatation/ aneurysm [43]. Ophthalmic examination described by Verkuil et al [54] showed right-eye abduction deficit, consistent with abducens palsy.…”
Section: Signs Symptoms and Physical Examinationmentioning
confidence: 99%
See 4 more Smart Citations
“…Respiratory symptoms were rare, usually presenting with cough or dyspnea [8,9,42,43,46,47,49,51,54,57,60,62,69], or rhinorrhea [42]. Cardiac dysfunction [6, 29,43,71] was seen, with chest pain [9, 50] on presentation, myocarditis [8,43], and coronary artery dilatation/ aneurysm [43]. Ophthalmic examination described by Verkuil et al [54] showed right-eye abduction deficit, consistent with abducens palsy.…”
Section: Signs Symptoms and Physical Examinationmentioning
confidence: 99%
“…Major treatment modalities were IVIG [6, 8, 28, 29, 40-46, 48-50, 52, 53, 55-63, 66-69, 72, 73], steroids [6, 8, 28, 29, 40-42, 44, 48, 49, 52, 59-61, 72, 73] like prednisolone [53,62], methylprednisolone [45,46,50,56,57,60,66,67], hydrocortisone [53,58], or dexamethasone [55], antiplatelet medications [6, 41,54] such as aspirin [43-45, 55, 58-61, 63, 66], and clopidogrel [45], and anticoagulation medications [6, 41,50,60] like enoxaparin [9, 41,47,50,56,58,67,70]. Vasoactive [6,9,40,47,54] and ionotropic agents [30,45,56,61] such as norepinephrine [41], dopamine [64,74], and milrinone [41,44,74] were added to treatment regimens when indicated. In a study by Greene A.G. et al, vitamin K [41] was indicated as well.…”
Section: Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations